Global patterns in testicular cancer incidence and mortality in 2020. Issue 5 (26th March 2022) - Znaor, Ariana; Skakkebaek, Niels Erik; Rajpert‐De Meyts, Ewa; Kuliš, Tomislav; Laversanne, Mathieu; Gurney, Jason; Sarfati, Diana; McGlynn, Katherine A.; Bray, Freddie
Abstract: With 74 500 new cases worldwide in 2020, testicular cancer ranks as the 20th leading cancer type, but is the most common cancer in young men of European ancestry. While testicular cancer incidence has been rising in many populations, mortality trends, at least those in high‐income settings, have been in decline since the 1970s following the introduction of platinum‐based chemotherapy. To examine current incidence and mortality patterns, we extracted the new cases of, and deaths from cancers of the testis from the GLOBOCAN 2020 database. In 2020, testicular cancer was the most common cancer in men aged 15 to 44 in 62 countries worldwide. Incidence rates were highest in West‐, North‐ and South‐Europe and Oceania (age‐standardised rate, ASR ≥7/100 000), followed by North America (5.6/100 000 and lowest (<2/100 000) in Asia and Africa. The mortality rates were highest in Central and South America (0.84 and 0.54 per 100 000, respectively), followed by Eastern and Southern Europe, and Western and Southern Africa. The lowest mortality rates were in Northern Europe, Northern Africa and Eastern Asia (0.16, 0.14, 0.9 per 100 000, respectively). At the country level, incidence rates varied over 100‐fold, from 10/100 000 in Norway, Slovenia, Denmark and Germany to ≤0.10/100 000 in Gambia, Guinea, Liberia, Lesotho. Mortality rates were highest in Fiji, Argentina and Mexico. Our results indicate a higher mortality burden in countries undergoing economic transitions and reinforce the need for more equitable access to testicular cancer diagnosis and treatment globally. Abstract : What's new? In this investigation of recent patterns in testicular cancer incidence and mortality worldwide, incidence rates were found to be highest in Europe, Oceania and North America and lowest in Asia and Africa. By contrast, mortality rates were highest in Latin America and in certain parts of Europe and Africa. Mortality burden was greatest in countries currently experiencing economic transition, highlighting the importance of equitable access to diagnostic and therapeutic resources for testicular cancer.